Axial compressive behavior of recycled aggregate concrete-filled square steel tube stub columns strengthened by CFRP. (February 2021) - Liang, Jiongfeng; Lin, Siqi; Li, Wei; Liu, Dawei
Abstract: Fiber-reinforced polymer (FRP)-confined recycled aggregate concrete-filled steel tube (RACFT) columns significantly mitigate the defects of RAC, and hence can be potentially used in structural engineering, e.g., column and pile. However, the existing studies on the behavior of recycled aggregate concrete-filled steel tube (RACFT) columns strengthened by the fiber-reinforced polymer (FRP) are scarce, especially those on square specimens. This paper presents an experimental study to investigate the compressive behaviors of FRP-confined RACFT square columns. The results in this paper suggest that the FRP-confined RACFT column with a higher RA replacement ratio has a smaller axial strength of the specimen, but tends to exhibit more ductile behavior. The specimen confined by a thicker FRP tends to have a higher axial strength and larger ultimate strain due to the better confinement effect of thicker FRP on the RACFT column. Additionally, compared with the partial wrapping scheme, the full wrapping scheme mainly improves the ductile behavior of the RACFT columns rather than their axial strengths. Based on the test results, a design model of the axial load bearing capacity for FRP-confined RACFT columns is proposed, which is found to predict the results of experimental tests accurately.